Brand Atlas : Branding intelligence made visible - Wheeler, Alina; Katz, Joel (Wiley, 2011)
"An innovative, full-color compendium to branding's best thinking from the world's leading brand strategists and practitioners A company's brand is its most valuable asset. Wheeler takes the most seminal tools used by a wide variety of thought leaders and practitioners and makes the information understandable, visible, relevant, exportable and applicable. With her best-selling debut book, Designing Brand Identity, now in its third edition, Alina Wheeler reinvented the marketing textbook using a straightforward style to help demystify the branding process. This new offering from Wheeler, Brand Atlas, builds on this user-friendly approach to aggregate and simplify the science behind branding with a unique visual teaching method suited for time-crunched professionals. Brand Atlas follows the recent YouTube-iPhone-Pecha Kucha era trend toward fast-paced visual instruction by neglecting needless jargon and combining vivid, full-color images and easy-to-follow diagrams to break down branding principles into basic step-by-step concepts that can be immediately applied. This handy reference: Speaks to a broad range of stakeholders in the branding process--from CEOs to designers to brand managers Provides tools to integrate brand throughout the entire customer experience, build relationships based on brand, measure a brand's value, and define a brand strategy Contains essential information illustrated through the use of diagrams With diagrams designed by Joel Katz, an internationally known information designer and a global authority on the visualization of complex information, Brand Atlas is a compact, no-nonsense guide that shows how tactical innovation in the design process is crucial to building brand assets"--Provided by publisher.